Invasive species in east Africa: current status for informed policy decisions and management - Gichua, M.; Njoroge, G.; Shitanda, D.; Ward, D. (E. Africa: Status and policy in biological invasions, 2013)
Invasive alien species are the second leading cause of biodiversity loss in the world today. A number of hypotheses have been advanced to explain the proliferation of invasive species. These hypotheses include deficiency of natural enemies in the introduced range, increased competitive ability, increased resource availability and emergence of more vigorous genotypes in the introduced range. In East Africa policy gaps that range from lack of information on invasive species management to how the available information is managed exist. Major gaps include, a deficiency in the number and interest of scientists studying invasion species biology, which subsequently leads to lack of interest in the learning institutions, severe deficiency in predictive and monitoring capacity, lack of coordinated control measures, and poor preparation in government departments. This report serves to identify the major gaps and provide information to assist in the prioritization and optimization of invasive species control and management. It recommends a need for scholars and institutions to develop curricula and recruit more scientists in this discipline. It also recommends an integrative approach, regional coordination and collaboration including sharing of information in an easy and practical language. The review further encourages the government and development agencies at the national and the local level to provide funding and incentives for low and localized programs to slow the spread of existing invasive species in order to protect the yet uninvaded ecosystems. The adaptation of these recommendations will result to control strategies and policy framework based on sound empirical information It is expected that the report will be valuable for land, environmental managers and other stakeholders
Keywords: Invasive species; East Africa; Policy; Management